Case history of therapeutic patient: manual - Oslopov, V. N. (GEOTAR-Media, 2014)
The manual provides a detailed plan of the case history with a sample of the case report of a patient with the pathology of the internal organs. The comments given for the proper understanding of the material highlight a number of issues which are diffi cult for the students starting their work at a hospital (state of consciousness, the defi nition of the general condition of the patient, etc.). Decoding and brief explanation of the abbreviations of laboratory blood and urine indices, determined by the means of modern analyzers, test questions with explanation of correct answers are given. The manual is intended for the 2nd and 3rd year students of the General Medicine faculty, but also is useful for senior students of medical universities.